Age-related variations in mental health and wellbeing during the first wave of the COVID-19 pandemic: a multi-country survey analysis - Foláyan, Moréniké Oluwátóyìn; Abeldaño Zuñiga, Roberto Ariel; Aly, Nourhan M.; Ellakany, Passent; Ezechi, Oliver Chukwujekwu; Gaffar, Balgis; Ibigbami, Olanrewaju Ibikunle; Idigbe, Ifeoma Eugenia; Ishabiyi, Anthonia Omotola; Khader, Yousef; Lawal, Folake Barakat; Lusher, Joanne; et al. (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic substantially impacted mental health. This study explored age-related differences in the mental health and wellbeing of participants during the initial wave of the COVID-19 pandemic.MethodsSecondary analyses of data from 21,106 participants collected between July and December 2020 across 152 countries was conducted. Multivariable logistic regression models were used to determine the relationship between the dependent variables and age after accounting for potential confounders. The dependent variables examined were emotional distress, social isolation, sleep pattern changes, sexual activity changes, financial security, housing and food insecurity, changes in family relationships, memory complaints, and post-traumatic stress syndrome (PTSS). Age groups were considered: young adults (18–24), adults (25–49), and older individuals (≥50). The confounding variables were sociodemographic variables namely: sex (male or female), marital status (single or has had a relationship), employment status (employed, unemployed, student, or retiree), educational status (none, primary, secondary, or college/university), country of residence income (low-income countries, lower-middle-income countries, upper-middle-income countries, and high-income countries) and pandemic stringency index indicating the comprehensiveness of pandemic policies adopted at country level.ResultsOf the 21,106 participants, 12,807 (60.7%) were aged 25–49. Compared to those over 50, 18–24-year-olds had significantly higher odds of increased sexual activity (AOR: 4.41), housing insecurity (AOR: 1.73), and PTSD (AOR: 3.22), but lower odds of social isolation (AOR: 0.66), food insecurity (AOR: 0.85), and memory complaints (AOR: 0.53). Similarly, 25–49-year-olds had higher odds of increased sexual activity (AOR: 2.65), housing insecurity (AOR: 2.28), food insecurity (AOR: 1.14), worsened family relationships (AOR: 1.15), and PTSD (AOR: 2.24), but lower odds of social isolation (AOR: 0.84), sleep disturbances (AOR: 0.82), and memory complaints (AOR: 0.81). Emotional distress and financial insecurity did not differ significantly across age groups.ConclusionThe study highlights age-specific variations in mental health challenges during the pandemic. The nuanced impact of age on mental wellbeing emphasizes the need for targeted interventions. Future research should explore the interplay between age, pandemic-related factors, and specific mental health outcomes to inform tailored support mechanisms for diverse age groups.